Novel Fluorinated Pyrazoline Based Ethers: Synthesis, Characterization and Antimicrobial Evaluation - Mustafa, Zheena Jabar; Salih, Twana Mohsin; Hawaiz, Farouq E. (Kurdistan Journal of Applied Research, 2025)
In response to the growing global threat of antimicrobial resistance, this work seeks to synthesize and analyze chalcone-derived pyrazoline derivatives and assess their antibacterial efficacy against the Staphylococcus aureus   and Escherichia coli).  A series of pyrazoline compounds were synthesized using both classical step-wise and one-pot synthetic strategies, involving Claisen–Schmidt condensation of 4-(4-fluorobenzyl) oxy acetophenone with various substituted benzaldehydes that subsequently undergo cyclization with phenyl hydrazine. The chemical structures of the produced chalcones and their corresponding pyrazolines were characterized using FTIR, ¹H-NMR, and ¹³C-NMR spectroscopy. Physicochemical characterization revealed the products were obtained in high yields and were sufficiently stable for isolation, with improved yields observed via the one-pot method. Antibacterial activity was assessed using the disk diffusion technique at multiple concentrations (200–800 ppm). The results demonstrated that pyrazoline derivatives exhibited significantly higher inhibition zones, particularly against S. aureus, compared to their chalcone precursors. Compounds 5a, 5c, and 5f had the most significant antibacterial efficacy, whereas chalcones showed minimal to no action against E. coli. The findings confirm the superior bioactivity of the pyrazoline ring system and suggest the crucial impact of electron- giving and electron-removing substituents on antibacterial potential. This research underscores one-pot synthesis as operationally simple and reducing waste generation by eliminating the need for intermediate isolation, thereby offering a more efficient and practical route, time-saving method for producing structurally varied, physiologically active pyrazolines, presenting attractive possibilities for the development of novel antibacterial medicines.